Selection of superior cowpea lines for multi-traits and adaptabilities to the Piauí semi-arid using genotype by yield*trait biplot analysis - Araújo, Mauricio dos Santos; Pinheiro dos Santos, Samiria; Lelis de Aragão, Walter Frazão; Damasceno-Silva, Kaesel Jackson; de Moura Rocha, Maurisrael (Editora UFLA, 2021)
Cowpea is a great socioeconomically important leguminous plant worldwide. The crop is an excellent source of proteins and minerals, mainly for the poorest populations. It is cultivated in some states of Brazil. The Piauí semi-arid is the most yielding zone in the state. Thus, the selection of superior cowpea genotypes for multi-traits and adaptabilities to this growing area is very important for the small-scale and medium-scale farmers in Piauí. The objective of this study was to select the superior cowpea lines for their multi-traits and adaptabilities to the Piauí semi-arid zone based on the genotype by the yield*trait (GYT) Biplot approach. Seventeen elite lines and three cultivars were evaluated in a randomized complete block design with four replications under the rainfed growing condition at three different locations away from the Piauí semi-arid zone. The following traits were evaluated: the number of days to flowering, pod length, the number of grains per pod, weight of one hundred grains, grain index, grain yield, Fe and Zn contents, and also the cooking quality. The analysis of variance (ANOVA), the grouping of means, and simultaneous selection by the GYT Biplot were implemented. Through the GYT Biplot approach, the two lines, MNC11-1013E-35 and MNC11-1013E-15, were found superior because they combined the traits, grain-yield with the yield components and nutritional traits simultaneously during the cultivation in the Piauí semi-arid zone. However, the MNC11-1052E-3 line was better in the combination of yield and cooking quality than the other lines.